Topographies of fascism : habitus, space, and writing in twentieth-century Spain - Santiáñez-Tió, Nil (Toronto Iberic., 2013)
"While Topographies of Fascism centres on Spain, a nation that produced a large number of fascist texts focused on space, it also draws on works written by key German, Italian, and French fascist politicians and intellectuals. Ultimately, it provides an innovative model for analysing the comparable yet often overlooked strategies of symbolic representation and production of space in fascist political and cultural discourse."--Jacket